2020
DOI: 10.1038/s41593-020-0666-y
|View full text |Cite
|
Sign up to set email alerts
|

Complementary contributions of non-REM and REM sleep to visual learning

Abstract: Sleep is beneficial for learning. However, it remains unclear whether learning is facilitated by non-REM (NREM) sleep or by REM sleep, whether it results from plasticity increases or stabilization, and whether facilitation results from learning-specific processing. Here, we trained volunteers on a visual task, and measured the excitatory and inhibitory (E/I) balance in early visual areas during subsequent sleep as an index of plasticity. E/I balance increased during NREM sleep irrespective of whether pre-sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
157
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(193 citation statements)
references
References 87 publications
12
157
2
Order By: Relevance
“…The involvement of brain activity during NREM sleep in the offline performance gains in VPL is consistent with the results of a recent study (Tamaki et al, 2020b). This study demonstrated that the visual plasticity indexed as an excitation and inhibition balance by magnetic resonance spectroscopy was increased during NREM sleep and was correlated with the offline performance gains in VPL (Tamaki et al, 2020b). The results together suggest that after visual training, visual plasticity increases in the early visual areas during posttraining NREM sleep to create a neural environment that promotes sigma activity in the early visual areas, leading to offline performance gains.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The involvement of brain activity during NREM sleep in the offline performance gains in VPL is consistent with the results of a recent study (Tamaki et al, 2020b). This study demonstrated that the visual plasticity indexed as an excitation and inhibition balance by magnetic resonance spectroscopy was increased during NREM sleep and was correlated with the offline performance gains in VPL (Tamaki et al, 2020b). The results together suggest that after visual training, visual plasticity increases in the early visual areas during posttraining NREM sleep to create a neural environment that promotes sigma activity in the early visual areas, leading to offline performance gains.…”
Section: Discussionsupporting
confidence: 92%
“…The involvement of brain activity during NREM sleep in the offline performance gains in VPL is consistent with the results of a recent study (Tamaki et al, 2020b). This study demonstrated that the visual plasticity indexed as an excitation and inhibition balance by magnetic resonance spectroscopy was increased during NREM sleep and was correlated with the offline performance gains in VPL (Tamaki et al, 2020b).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations